SME Competitiveness Cluster Analysis in East Java - Muslih, Muslih; Erlando, Angga (Journal of Developing Economies, 2019)
This study aims to analyse the competitiveness of the small and medium industries in East Java in the face of global economic openness. The method used is a cluster to find out the factors that influence the competitiveness of Small and Medium Industries (SME) by grouping them into groups based on similarity of characters. The use of the cluster method is carried out hierarchically, or processed through a series of successively fusing objects into groups. Based on the results of identification and analysis, then the conclusion, there are three cluster findings based on competitiveness categories. Cluster I is SME with low competitiveness, Cluster II is SME with high competitiveness, and Cluster III is SME with medium competitiveness. SME that have high competitiveness are SME that can increase efficiency in 2 fields, namely Production and Marketing. While SME that have medium competitiveness are SME that are superior in technology, so they can be classified in the creative industry.   Keywords: Competitiveness, Cluster, SME, East Jawa JEL Classification: O0; O1; O2; L6